2019
DOI: 10.1186/s42269-019-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biosurfactant from Citrobacter freundii MG812314.1 as a bioremoval tool of heavy metals from wastewater

Abstract: Background: The problem of heavy metal contamination is a global issue, and the challenge is to develop methods to remove heavy metals from soil and water. Recently, biosurfactants are one of the compounds that provide an attractive eco-friendly alternative to the physicochemical process in alleviating the heavy metals. Results: Sixty bacterial isolates were isolated from Al-Rahawy drain sediments and screened for biosurfactant production. Only 10 isolates were recoded as biosurfactant producers by the oil spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The removal efficiency of lead ions increased gradually with the increase of contact times up to 80 min and almost constant at 100 min. Similarly, previous study also demonstrated that higher removal efficiency also increased with the increase in contact time [21]. It is also believed that the surface binding promoted fast initial metal biosorption rate while the following slower sorption was related to the interior penetration.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The removal efficiency of lead ions increased gradually with the increase of contact times up to 80 min and almost constant at 100 min. Similarly, previous study also demonstrated that higher removal efficiency also increased with the increase in contact time [21]. It is also believed that the surface binding promoted fast initial metal biosorption rate while the following slower sorption was related to the interior penetration.…”
Section: Discussionsupporting
confidence: 57%
“…The changes on the surface structures of biosorbent can be observed directly by SEM. Biosorbent were centrifuged at 2,400 x g for 10 min, followed by washing three times with aquabidest for SEM analysis, then the pellets were applied onto a copper grid coated with carbon onto these pellets prior to observation under SEM-EDX (Hitachi SU 3500) [21].…”
Section: Sem-edx Analysismentioning
confidence: 99%
“…In other study, Zhang et al [78] showed that the treatment of landfill leachate with wastewater using a microbial consortium composed of the bioflocculant-producing strains Bacillus cereus and Pichia membranifaciens enabled the removal of 73% of COD. In turn, Gomaa and El-Meihy [79] reported a great capacity of biosurfactant produced by Citrobacter freundii MG812314.1 to remove the heavy metals from wastewater. Our research revealed that two of the ten bioaugmentation candidates, namely R. erythropolis KB4 and P. putida N6, had weak bioflocculation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also report biosurfactant production by Paenibacillus alvei [42], Paenibacillus sp. [43], Citrobacter murliniae [44], and Citrobacter freundii [45].…”
Section: Discussionmentioning
confidence: 99%